[Рец.]: Moon, David. The American Steppes: The Unexpected Russian Roots of Great Plains Agriculture, 1870s–1930s. Cambridge: Cambrige University Press, 2020. xxxiii + 432pp. (Zaporizhzhia Historical Review, 2022)
-